Transcriptomics and single cell sequencing revealed the important role of PPAR signaling pathway in zebrafish liver fibrosis induced by thioacetamide - Yilong Cui; Mula Na; Xinxin Zhang; Jie Wang; Lei Song; Qianxun Wang; Chi Feng; Xiaodong Hu; Jianhua Yu; Guiying Kang; Wu Dong; Jingfeng Yang (Environmental Pollution, 2026)

Large language model orchestrated workflow integrating retrieval-augmented generation and model context protocol tools for urban-scale simulation-based resilience assessment - Jingfeng Zhou; Jiying Chen; Meng Wang; Baihua Dong; Xiaochi Zhou (Building and Environment, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Pre-occupation strategy towards high initial coulombic efficiency in Mn-based layer cathode for magnesium-based hybrid-ion batteries - Yipeng Liu; Baihua Qu; Junhao Zhang; Hongfei Zheng; Le Tong; Yue Hao; Dong Wang; Guangsheng Huang; Qian Li; Xiaoyuan Zhou; Dong-Liang Peng; Jingfeng Wang (Chemical Engineering Journal, 2025)

The impact of selenium fertilizer application on the yield, quality, and selenium accumulation characteristics of sweet potato - Huifeng Li; Yixuan Zhang; Yanqing Li; Yongmei Huang; Jingfeng Hua; Jie Yin; Dong Xiao; Tianyuan Chen (Acta Physiologiae Plantarum, 2025)

Pilot-scale application of sludge fermentation-driven nitrogen removal process with rapid in-situ enrichment of anammox bacteria for sustainable treatment of municipal wastewater and excess sludge - Shiwei Hao; Li Zhang; Jingfeng Gao; Xuepeng Fan; Tingjun Dong; Jiachun Yang; Shuang Lan; Yongzhen Peng (Chemical Engineering Journal, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Differential responses of plant and microbial respiration to extreme precipitation and drought during spring and summer in the Eurasian meadow steppe - Tsegaye Gemechu Legesse; Jingfeng Xiao; Gang Dong; Xiaobing Dong; Nano Alemu Daba; Guta Wakbulcho Abeshu; Luping Qu; Wen Zhu; Lulu Wang; Xiaoping Xin; Changliang Shao (Environmental Research, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Genomic synergistic efficient carbon fixation and nitrogen removal induced by excessive inorganic carbon in the anammox-centered coupling system - Shiwei Hao; Li Zhang; Jingfeng Gao; Tingjun Dong; Yongzhen Peng; Akira Miyazawa (Water Research, 2024)

Residual stress tests and predictive model of friction stir welded normal-strength aluminium alloy H-shaped sections - Beibei Li; Guoqiang Li; Jingfeng Wang; Boshan Chen; Yuanqing Wang; Yecheng Dai; Gang Dong (Engineering Structures, 2024)

Soil environmental anomalies dominate the responses of net ecosystem productivity to heatwaves in three Mongolian grasslands - Lu-Ping Qu; Gang Dong; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Jingyan Chen; Shicheng Jiang; Ochirbat Batkhishig; Tsegaye Gemechu Legesse; Xiaoping Xin; Changliang Shao (Science of The Total Environment, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Polymer surfactants as viscosity reducers for ultra-heavy oil: Synthesis and viscosity reduction mechanism - Xiaojun Zhang; Jixiang Guo; Dongtao Fei; Li Wang; Zhongying Peng; Jianmin Li; Jingfeng Dong (Fuel, 2024)

Research for inclusive quality education: Leveraging belonging, inclusion, and equity Research for inclusive quality education: Leveraging belonging, inclusion, and equity , edited by Christopher Boyle and Kelly-Ann Allen, Singapore, Springer, 2023, 313 pp., € 129.99 (hardback), ISBN 9789811659072 - Jingfeng Yue; Xiaobo Dong (The Social Science Journal, 2024)

Integration of harvester trajectory and satellite imagery for large-scale winter wheat mapping using deep positive and unlabeled learning - Xingguo Xiong; Jie Yang; Renhai Zhong; Jinwei Dong; Jingfeng Huang; K.C. Ting; Yibin Ying; Tao Lin (Computers and Electronics in Agriculture, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Aflatoxin B1-induced early developmental hepatotoxicity in larvae zebrafish - Chi Feng; Hongxia Bai; Xu Chang; Zhixuan Wu; Wu Dong; Qianqian Ma; Jingfeng Yang (Chemosphere, 2023)

Revisiting the role of transpiration in the variation of ecosystem water use efficiency in China - Huaiwei Sun; Mengge Lu; Yong Yang; Jianing Chen; Jingfeng Wang; Dong Yan; Jie Xue; Wenxin Zhang (Agricultural and Forest Meteorology, 2023)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Removal of hexavalent chromium from water by modified sponge iron particles and insights into mechanism - Guilin Zhu; Junde Song; Weihong Dong; Jingfeng Lu; Yan Wang; Weinan Jiang; Ping Guo (Environmental Science and Pollution Research, 2018)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Aqueous Solution of Anionic Surfactants Mixed with Soils Show a Synergistic Reduction in Surface Tension - Kerstin Hagenhoff; Jingfeng Dong; Babur Z. Chowdhry; Stephen Anthony Leharne (Water, Air, & Soil Pollution, 2010)